Using java language for control algorithms - Silva, Valter (2002)
constrained resources devices used often in embedded systems are normally programmed using languages considered of low level. This has important implications in program development and maintenance. In fact, the code becomes less legible and the memory management in not an easy task. This problem can be overcome if the use of a high level language with garbage collector mechanism is considered. However, it is often a belief that from these high level languages results slowly programs, and so, they are unsuitable for embedded applications. In this paper this problem is addressed to show the applicability of Java to develop programs for constrained resources devices. An example of a control system for temperature control is presented to illustrate the advantages of the approach.